Radio spectrum reforms and associated effects on market liberalisation - Lesufi, Cynthia Leungo (My University, 2016)
There is a common opinion among researchers and experts that efficient management of radio spectrum plays a vital role in ensuring universal access to telecommunications services. The objective of this study was to identify radio spectrum reforms and their associated effects on market liberalisation. It was postulated that appropriate radio spectrum reforms would be catalysts for market liberalisation. The evolution of command-and-control approaches in relation to market-based approaches was assessed. The research involved literature critique, review of policies as that relates to history of radio spectrum management in South Africa and across the world, and radio spectrum regulations analysis in South Africa. Interviews of radio spectrum industry experts and documents study of the evolution of telecommunications regulatory environment with respect to radio spectrum management and market liberalisation were also used as main sources of research. The purpose of the literature critique, review of policies, regulations and documents was to identify hints of radio spectrum reforms and measure qualitatively the extent of market liberalisation. While interviews of radio spectrum industry experts were used to ascertain industry response to strides made as far as radio spectrum and market liberalisation in South Africa. It was observed that initially, in most parts of the world and in South Africa, market liberalisation progressed quickly despite appreciable correlation with radio spectrum reforms. Early radio spectrum reforms, such as the establishment of an independent regulator of the industry and radio spectrum, had contributed to some level of market liberalisation with creation of oligopolistic telecommunication market, and had increased to radio spectrum by Vodacom, MTN and Cell C having access to both 900 MHz and 1800 MHz bands. However, perpetual practise of command-and-control, an efficient radio spectrum management encouraged hoarding. The literature review and interview provided seven main contributions of reforms in the form of strides. These strides formed the basis for the research framework: 1) establishment of an independent regulator of the industry and radio spectrum, 2) increased access to radio spectrum, 3) service and technology neutrality on radio spectrum, 4) essential facilities to enable sharing, 5) market-based approaches radio spectrum pricing: AIP, 6) service-based competition versus infrastructure-based competition, and 7) non-rival, non-exclusive usage of radio spectrum. The conclusion is that increasing access to radio spectrum and the independent regulator were not primary determinants of market liberalisation. An analytic framework has been used to show that market liberalisation reached a plateau phase, with a few incumbents becoming dominant and creating an oligopolistic market structure. It is at this point that further market liberalisation could be stimulated by additional radio spectrum reforms. The command-and-control approach remains the main bottleneck source for access and efficiency in radio spectrum management, which encourages rival and exclusive use of radio spectrum. It has been observed that market-based radio spectrum reforms have also entrenched rivalry and exclusivity in the use of radio spectrum. Radio spectrum reforms that encourage non-rivalry and non-exclusivity, such as open-access to radio spectrum, are highly recommended in this research.
A thesis submitted in fulfilment of the requirements for the degree of Master of Arts, in ICT Policy and Regulation, University of the Witwatersrand, 2016
Keywords: Radio frequency allocation--Management; Radio resource management (Wireless communications); Telecommunication policy--South Africa; Wireless communication systems; Free trade